The role of convalescent plasma and hyperimmune immunoglobulins in the COVID-19 pandemic, including implications for future preparedness - So-Osman, Cynthia; Burnouf, Thierry; Al-Riyami, Arwa Z.; Bloch, Evan M.; Estcourt, Lise; Goel, Ruchika; Tiberghien, Pierre; Vermeulen, Marion; Wendel, Silvano; Wood, Erica M. (Frontiers in Immunology, 2024)
Introduction When Coronavirus Disease-19 (COVID-19) struck the world in December 2019, initiatives started to investigate the efficacy of convalescent plasma, a readily available source of passive antibodies, collected from recovered patients as a therapeutic option. This was based on historical observational data from previous virus outbreaks. Methods A scoping review was conducted on the efficacy and safety of convalescent plasma and hyperimmune immunoglobulins for COVID-19 treatment. This review included the latest Cochrane systematic review update on 30-day mortality and safety. We also covered use in pediatric and immunocompromised patients, as well as the logistic challenges faced in donor recruitment and plasma collection in general. Challenges for low resource countries were specifically highlighted. Results A major challenge is the high donation frequency required from first-time donors to ensure a safe product, which minimizes the risk of transfusion-transmitted infectious. This is particularly difficult in low- and middle- income countries due to inadequate infrastructure and insufficient blood product supplies. High-certainty evidence indicates that convalescent plasma does not reduce mortality or significantly improve clinical outcomes in patients with moderate to severe COVID-19 infection. However, CCP may provide a viable treatment for patients unable to mount an endogenous immune response to SARS-CoV-2, based on mostly observational studies and subgroup data of published and ongoing randomized trials. Convalescent plasma has been shown to be safe in adults and children with COVID-19 infection. However, the efficacy in pediatric patients remains unclear. Discussion Data on efficacy and safety of CCP are still underway in ongoing (randomized) studies and by reporting the challenges, limitations and successes encountered to-date, research gaps were identified to be addressed for the future. Conclusion This experience serves as a valuable example for future pandemic preparedness, particularly when therapeutic options are limited, and vaccines are either being developed or ineffective due to underlying immunosuppression.